The Tooth and Skin Colour Interrelationship across the Different Ethnic Groups - Satheesh B. Haralur; Ahmed Mohammed Dibas; Nabil Abdullah Almelhi; Dhafer Ali Al-Qahtani (International Journal of Dentistry)
Objectives. The purpose of the study was to investigate the relation between skin and tooth colour parameters in various ethnic groups. Materials and Methods. Saudi Arabian, Indian, African, and East Asian ethnic groups of 75 each were included in the study. The tooth colour was determined by spectrophotometer in CIELAB parameters. The skin colour was measured at earlobe, forehead, and malar locations by clinical skin photography. The data was statistically analysed by one-way ANOVA and correlation tests. Results. The “L” vale for the Saudi Arabian group had a strong correlation at earlobe location (r=0.275), while correlation was found at forehead (r=0.271) and malar region (r=0.261) with Indian ethnic group. A strong negative correlation was observed in African ethnic group at all three locations for “L” parameter. The redness value “a” is found to have strong negative linear correlation between the earlobe and tooth for Saudi Arabian (r=-0.240) and Indian ethnic groups (r=-0.268). The “b” showed no correlation with skin location in all groups except positive correlation in African ethnic groups. Conclusions. The strong correlation was found between the skin and tooth colour parameters; hence the skin colour can be used as a guide for artificial tooth selection in edentulous patients.